Ragam Makna Asosiatif pada Kumpulan Cerpen Malam Terakhir Karya Leila S. Chudori - Ayda Nur Haliqa; Dodi Fimansyah; Jumiati Mukaromah Safira; Zahrotul Husna (Pusat riset dan Inovasi Nasional, 2025)
This article aims to: (1) explain the associative meaning contained in the story collection titled Malam Terakhir by Leila S. Chudori, (2) describe the associative meaning contained in the story collection. This research uses a qualitative approach with a descriptive method. The main source of data in this study is the story collection Last Night written by Leila S. Chudori. The data collection process was carried out using reading and note-taking techniques. Data validation was carried out through increased diligence, discussions with peers, and using the triangulation method. Data analysis was conducted in three steps, namely data reduction, data presentation, and conclusion drawing. The findings of this study show that the associative meaning in the story collection Last Night by Leila S. Chudori is 54 data, which is divided into four groups: stylistic meaning with 16 data, affective meaning contains 10 data, connotative meaning includes 17 data, and collocative meaning totals 11 data. Based on the analysis, it is concluded that the texts in the story collection Last Night by Leila S. Chudori contain vocabulary that has associative meaning.